Uma investigaç\~ao sobre a desigualdade na distribuiç\~ao de renda e o endividamento dos trabalhadores Norte-Americanos dos anos 1980 aos anos 2000 - Lucas Azeredo da Silva Teixeira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The purpose of this paper is to discuss the origins of a critical process in the North American economy before the subprime crisis, namely, the increasing debt of households. It is argued that causes of this indebtedness are alterations in income distribution (an increased concentration of income) and the process of financial deregulation and innovation, developed in the late 1970s. Considering that the latter has previously been explored in great detail, this particular examination explores the changes on income distribution pattern. Based on this perspective, it is concluded that the indebtedness does not come from families or households in general but, more specifically, from North American workers, who had to finance their spending through an on-going stagnation, or even deterioration, of the real wages at their disposal. Further, the direction of the North American economy after the crisis is evaluated in the contexts of these findings.
Keywords: E24; E25; E60; J31; D63; 330